Vikram Seth’s A Suitable Boy: A Pen Picture of Socio-Cultural Crisscross of Post-Colonial India - Dr Jyoti Patil, (The Creative Launcher, 2018)
Vikram Seth’s prodigious and brilliant literary journey so far has encompassed several books of poetry, a travelogue, a verse novel, an epic novel, modernist fiction and a memoir-cum biography. Each book is set in a different cultural landscape and background in terms of form and genre. Every new book of Seth creates a fresh departure in form and theme. His first novel, The Golden Gate (1986) in verse about the lives of young professionals in San Francisco, established him commercially as one of the promising Indian English writers. A Suitable Boy (1993), his 1474 page voluminous second novel as a postcolonial narrative deals with the socio-political issues that covers the issues of national politics, elections in 1952, inter-sectarian animosity, the status of lower caste people, land reforms and the eclipse of feudal princes and landlords amidst four family saga. This paper is an attempt to re-examine Vikram Seth’s A Suitable Boy as a pen-picture of Socio-Cultural Crisscross of postcolonial India and its varied ramifications in the socio-political realms. The many different themes and episodes discussed here present an all-inclusive idea of socio-cultural crisscross with all its plurality, challenges and shortcomings to present my views and reading of A Suitable Boy as an authentic picture of post-independence India.